2019
DOI: 10.21037/atm.2019.10.38
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of comprehensive intervention programs to control blood glucose in overweight and obese type 2 diabetes mellitus patients based on a real-world setting: Markov modeling

Abstract: Background: Blood glucose control management in overweight and obese diabetic patients poses heavy public health and economic burdens on the health system. This study aimed to evaluate the short-term costeffectiveness of a comprehensive intervention program for blood glucose management in different groups using a Markov model. Methods:Based on real-world data, a Markov model was developed to calculate the cost per qualityadjusted life-year (QALY) gained. The division of Markov states was in accordance with cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Most patients have type 2 DM (T2DM). In the past decade, the overall prevalence of DM among Chinese adults has been between 9.7% and 11.6% (2)(3)(4). DM has become a severe disease and poses a significant economic burden on the Chinese Government and its citizens (5).…”
Section: Introductionmentioning
confidence: 99%
“…Most patients have type 2 DM (T2DM). In the past decade, the overall prevalence of DM among Chinese adults has been between 9.7% and 11.6% (2)(3)(4). DM has become a severe disease and poses a significant economic burden on the Chinese Government and its citizens (5).…”
Section: Introductionmentioning
confidence: 99%
“…A careful search on Google Scholar of articles on pharmacoeconomic analysis on obesity in China (search keywords: pharmacoeconomic AND obesity AND China) published during 2010-2020 yielded 4,250 hits, but only five studies were identified by two of the co-authors as relevant, with obesity as the primary condition studied and China as the study setting [6,[39][40][41][42].…”
Section: Scoping Reviewmentioning
confidence: 99%
“…Another Markov modeling study found that the comprehensive intervention program for blood glucose management of overweight and obese patients with diabetes is cost-effective for the middle-aged male group (ICER of RMB104,000, or $15,147 in 2018US$, per QALY gained) and elderly female group, respectively [42].…”
Section: Cost-effectiveness Analyses Of Obesity Treatmentmentioning
confidence: 99%
“…A morbidly obese person is one with a body mass index (BMI) of 35 kg/m 2 or more. China was found by the global population weight survey to have one of the most morbidly obese populations in the world (1). At present, a single dose of propofol is used clinically to induce anesthesia.…”
Section: Introductionmentioning
confidence: 99%